Computational experiment of reinforced concrete structural elements using damage mechanics - Liu, Yu. (2008)
The finite element method (FEM) has been widely used to study the behaviour of reinforced concrete (RC) members and structures. However, the complex material properties of concrete and bond-slip behaviour of concrete-rebar interface and the difficulty in FEM modeling of the RC members with complicated rebar arrangement are still the two main problems in the three-dimensional FEM analysis of RC members.